2010
DOI: 10.1007/s11940-010-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Antiepileptic Drugs: When and Why?

Abstract: Opinion statementAfter a patient has initiated an antiepileptic drug (AED) and achieved a sustained period of seizure freedom, the bias towards continuing therapy indefinitely can be substantial. Studies show that the rate of seizure recurrence after AED withdrawal is about two to three times the rate in patients who continue AEDs, but there are many benefits to AED withdrawal that should be evaluated on an individualized basis. AED discontinuation may be considered in patients whose seizures have been complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
0
38
0
1
Order By: Relevance
“…It is also possible that exposure misclassification may have played a role in the differences. In the CPRD, the prescription records did not appear to allow for a tapering of dose and in epilepsy AEDs are not routinely discontinued abruptly and tapering can take a number of months [18]. Manual review of the electronic prescription records for the nine NDD cases of WWE and reportedly no AED exposure demonstrated that two women had been estimated to have discontinued valproate just prior to pregnancy; however, if tapering of the dose did occur rather than an abrupt stop (as predicted by the algorithm), their window of exposure could have been extended to overlap with early gestation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that exposure misclassification may have played a role in the differences. In the CPRD, the prescription records did not appear to allow for a tapering of dose and in epilepsy AEDs are not routinely discontinued abruptly and tapering can take a number of months [18]. Manual review of the electronic prescription records for the nine NDD cases of WWE and reportedly no AED exposure demonstrated that two women had been estimated to have discontinued valproate just prior to pregnancy; however, if tapering of the dose did occur rather than an abrupt stop (as predicted by the algorithm), their window of exposure could have been extended to overlap with early gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, the bias is toward an increased risk of seizure recurrence following AED discontinuation [28]. Both randomized controlled trials and prospective studies have demonstrated that adult patients with known epilepsy who continue AED treatment have relapse rates of 22-28%, compared with 41-50% in withdrawal groups [29,30] although lower seizure relapse rates of 15% have been reported in AED withdrawal groups [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of AED discontinuation have often concerned withdrawal of AED treatment, particularly for patients in remission . The present study, however, investigates the question of discontinuation after introduction of an AED, and adds to the evidence that polypharmacy may be unnecessary .…”
Section: Discussionmentioning
confidence: 99%